Building Reading Interest of Kamoro Tribe Children in Pigapu Village, Mimika Regency, Central Papua - Tebay, Vince; Ratang, Sarlota Arrang (Jurnal Pengabdian Masyarakat Bestari, 2024)
This service activity was carried out to increase the reading interest of Kamoro tribal children in Pigapu Village, most of whom are fishermen's children. The method used in this service is to provide understanding to teaching volunteers so that they are able to transfer knowledge to children through activities at the Aweida Reading Park. In addition, questionnaires were distributed to get responses from participants related to the topic of the activity to be carried out. As a result of the service carried out through training at the Aweida Reading Park, the children's interest in reading in Pigapu Village ran smoothly and the participants enthusiastically followed. In training and evaluation, the participants are quite immersed in this activity. The training activity not only involves the teachers of the reading park, but also children and parents who take their time to attend this activity.